Homecare Utilization Funnel among Discharged Patients at University of Airlangga Hospital - Elita Novriana Enisa; Djazuly Chalidyanto; Muhammad Ardian Cahya Laksana; Pipit Festi Wiliyanarti (PT.Mantaya Idea Batara, 2026)
Background: Although homecare is increasingly recognized as an extension of hospital services, limited evidence exists on the operational pathway from identifying potential patients to the actual utilization of homecare following discharge. Objective: to audit the promotion and utilization funnel of Universitas Airlangga Hospital homecare services among discharged patients from July 2025 to March 2026. Methods: This retrospective descriptive operational audit examined aggregate secondary data from daily homecare operational reports at Universitas Airlangga Hospital between July 2025 and March 2026. The daily report served as the unit of analysis rather than individual patients. Variables included the number of potential homecare patients, documented offer status, willingness responses, realized visits, service-unit origin, and service-category mentions. Data were analyzed descriptively using frequencies, percentages, and utilization ratios Result: Over 181 reporting days, 1,007 potential homecare patients and 235 realized homecare visits were identified, corresponding to 23.3 visits per 100 potential patients. In 2025, documented offer status was available for 121 of 656 potential patients (18.4%), of whom 97 (80.2%) had been offered homecare services. Among those offered, 2 (2.1%) were willing to order the service, 94 (96.9%) were still considering, and 1 (1.0%) declined at initial contact. Offer-response variables were not available in the 2026 reporting format. Physiotherapy or medical rehabilitation accounted for the largest proportion of service-category mentions (60.6%), followed by physician or specialist visits (16.5%). Conclusion: Homecare services at Universitas Airlangga Hospital exhibited substantial post-discharge demand; however, incomplete documentation limited the ability to observe the utilization funnel. Implementing a standardized homecare dashboard integrated with discharge planning could enhance monitoring, follow-up, and evaluation of homecare service utilization.